2020
DOI: 10.2147/jmdh.s238113
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mental Distress and Associated Factors Among Undergraduate Engineering Students of Hawassa University, Ethiopia</p>

Abstract: Background: Mental distress is a range of symptoms and experiences of a person's internal life that are commonly held to be troubling, confusing or out of the ordinary. Mental distress often interferes with studying, social interaction, and academic outcomes. Therefore, this study aimed at assessing the prevalence of mental distress and factors associated with it among undergraduate engineering students at Hawassa University. Methods: We conducted an institution-based cross-sectional descriptive study on under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…This study also found that mental distress associated with religious practice, even though most literature didn't consider religion as a variable. Students who were involved in the religious program, irrespective of what religion they follow, were less likely to develop mental distress, and consistent with studies done in Ethiopia (15,29). This might be because of religious teachings and doctrines helps students with stress management.…”
Section: Discussionsupporting
confidence: 77%
“…This study also found that mental distress associated with religious practice, even though most literature didn't consider religion as a variable. Students who were involved in the religious program, irrespective of what religion they follow, were less likely to develop mental distress, and consistent with studies done in Ethiopia (15,29). This might be because of religious teachings and doctrines helps students with stress management.…”
Section: Discussionsupporting
confidence: 77%
“…The level of Social support of the respondents was measured by Oslo 3-items social support scale. The tool was validated and has been used in previous studies in Ethiopia [58][59][60]. In this study, the tool had Cronbach's α score of 0.91.…”
Section: Data Collection Procedures and Toolsmentioning
confidence: 99%
“…These stressors and challenges may impair their learning capacity and academic achievement (Balaji et al, 2019;Gedam et al, 2020;Sridar, 2018). Academic factors (Bisai & Chaudhary, 2017;Gedam et al, 2020;Navarro-Martínez et al, 2020;Reddy et al, 2018;Sridar, 2018) and financial problems (Othman & Rashid, 2018;Negi et al, 2019;Reta et al, 2020;Gedam et al, 2020) have been identified to be the most frequent sources of stress for university students. Other than these common stressors, environmental factors, interpersonal relationships (Balaji et al, 2019), financial management issues, shifts in the living environment such as staying away from family, and challenges balancing personal and academic life also causes stress to university students (Navarro-Martínez et al, 2020;Reddy et al, 2018).…”
Section: 10 Introductionmentioning
confidence: 99%